Pampered to death : a Jaine Austen mystery - Levine, Laura, 1943- (Levine, Laura, 1943- Jaine Austen mystery., 2011)
Jaine Austen is looking forward to an indulgent spa getaway until she learns it is more about deprivation than relaxation. Between miniscule meals and a deadly brush with fame, surviving this vacation will be no piece of cake. When Jaine's friend Lance surprises her with a trip to The Haven, an uber-luxe health spa on the California coast, she and her feline pal Prozac are eager to hit the road and bask in a week of pampering and pedicures. But upon their arrival, she discovers that this oasis in the hills is merely a fat farm in disguise, complete with celery juice cocktails, humiliating weigh-ins, and a zero-tolerance position on carbs. And as she gets to know her fellow inmates, she realizes 300-calorie dinners are not the craziest thing she will be dealing with. Among her bulge battling companions is Mallory Francis, a B-list movie star with a knack for making frenemies with everyone she meets. When she is found strangled during a seaweed wrap gone awry, Jaine is hard-pressed to think of anyone who could not have done it. Perhaps it was Kendra, Mallory's bitter sister and personal assistant. Or maybe Clint, a macho former co-star whose dirtiest secret is in danger of being undressed in the drama queen's upcoming memoir. Or was it The Havens' pretty young masseuse, driven to commit a crime of passion when Mallory seduced her aerobics instructor husband Sven? With the suspects mounting faster than her hunger pangs, Jaine doesn't know who to believe. And when her search for truth, justice and contraband calories leads her straight to the cold-blooded killer, it seems murder may be on the menu once again.